Compactifications of the heterotic string with unitary bundles - Weigand, Timo (Fortschritte der Physik, 2006)
We describe a large new class of four-dimensional supersymmetric string vacua defined as compactifications of the E8 × E8 and the SO(32) heterotic string on smooth Calabi-Yau threefolds with unitary gauge bundles and heterotic five-branes. The conventional gauge symmetry breaking via Wilson lines is replaced by the embedding of non-flat line bundles into the ten-dimensional gauge group, thus opening up the way for phenomenologically interesting string compactifications on simply connected manifolds. After a detailed analysis of the four-dimensional effective theory we exemplify the general framework by means of a couple of explicit examples involving the spectral cover construction of stable holomorphic bundles. As for the SO(32) heterotic string, the resulting vacua can be viewed, in the S-dual Type I picture, as a generalisation of magnetized D9/D5-brane models. In the case of the E8 × E8 string, we find a natural way to construct realistic MSSM-like models, either directly or via a flipped SU(5) GUT scenario.
Gesehen am 09.01.2018